PENGARUH KECERDASAN INTELEKTUAL, KEMAMPUAN FISIK DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI SPRIPIM POLDA SULAWESI SELATAN - Ramli, Muh; Nurdin, Nurdin; Dangkeng, Arianto; Sudirman, Nengsi; Nurfaisah, Nurfaisah; Rifqiansyah, Rifqiansyah; wijaya, Hasrul (Jurnal Ilmu Manajemen Profitability, 2020)
The research aims to: 1) analyze the influence of intellectual intelligence on the performance of the Spripim Polda of South Sulawesi employees; 2) analyzing the influence of physical ability to the performance of officers Spripim Polda South Sulawesi; 3) Analyzing the influence of emotional intelligence on the performance of Spripim Polda South Sulawesi employees; 4) Analyzing the factors which are dominant influence on the performance of officers Spripim Polda South Sulawesi. The population of this research is all employees of the Spripim Polda South Sulawesi, amounting to 81 people with a whole sample or a saturated sample. The results showed that the influence coefficient of intellectual intelligence on employee performance is 0.330 with the value p = 0.012 < 0.05 This suggests that intellectual intelligence has a significant positive effect on employee performance. Influence coefficient of physical ability to employee performance of 0.138 with value p = 0.033 < 0.05. This suggests that physical abilities have a significant positive effect on the employee's performance, the influence coefficient of emotional intelligence Ssterhadap employee performance of 0.584 with a value of P = 0.000 < 0.05. This suggests that emesional intelligence has a significant positive effect on employee performance, and the highest beta value is an emotional intelligence variable with a beta value of 0.532. This indicates that the dominant influential variable affects the employee's performance as a variable of emotional intelligence.